Reflexives: Escaping exemption via domain reshuffling - Branco, António (Proceedings of the 12th International Conference on Head-Driven Phrase Structure Grammar, 2005)
In this paper we argue that at least for some languages, whenthere are suitable o-commanders of its selectional domain, areflexive in the bottom of its obliqueness hierarchy escapesexemption via a reshuffling of its local binding domain. Theoutcome of such reshuffling is that the local domain extends toinclude o-commanders of the reflexive in the subcategorizationdomain immediately upstairs, that is in the domain whose headpredicator directly subcategorizes the domain headed by thepredicator directly subcategorizing the reflexive.